Employee Performance: The Role of Compensation, Motivation, and Discipline as Intervening in the Era of the Industrial Revolution 4.0 - Misna Ariani; Didik Hadiyatno; Dwinda Tamara; Imam Arrywibowo; Farrah Diba Safira Yasmin (Universitas Mercu Buana, 2023)
Objective: This research investigates the relationship and impact of motivation, compensation, and work discipline on the performance of employees at a leading telecommunications company in Balikpapan, Indonesia within the context of the Industrial Revolution 4.0.Methodology: Data collection was conducted by sampling the entire population of 113 employees through observation and closed questionnaires. The hypothesis was tested using Smart-PLS.Finding: The independent variables of compensation and motivation demonstrate a significant positive impact on the dependent variable of employee performance. Moreover, compensation and motivation also significantly and positively affect the intervening variables of discipline. The disciplinary variables exhibit a significant positive influence on employee performance. Additionally, discipline plays a crucial role in mediating the relationship between compensation and motivation, leading to enhanced employee performance.Conclusion: Discipline, motivation, and compensation directly affect employee performance while motivation and compensation indirectly influence performance through the mediating effect of discipline. By fostering integrity, employees can enhance their performance and effectively confront the challenges posed by technological advancements in the digital world.